The Effect of English Song Media on Students' Vocabulary Pronunciation - Munir, Munir; Zalsabila, Alya (Har Press Indonesia, 2023)
Language is a communication tool that plays an important role in human life. By using language, one can relate to other people. Pronunciation is very important in vocabulary development because it involves distinguishing between sounds that combine to form words and concepts. Observations are carried out by observing and carefully recording events in the classroom, which occur during the interaction of all participants in the learning process at school. This study chose class IX students because the age level of these students is usually students who are less interested in learning one language, especially English. This research was conducted in four meetings. The results of the study indicate that the results of interviews that have been conducted by researchers indicate that the answers received by researchers indicate that students are very motivated and happy in learning English by using the media song. In addition, based on the results of observations and actions taken by researchers in using song media in teaching and learning activities, shows that students have succeeded in bringing about changes in how to pronounce the vocabulary spoken in every word tested. The important aspect of influencing the nation's vision and mission. Education is the key to a better future. Pronunciation is very important in vocabulary development because it involves distinguishing between sounds that combine to form words and concepts.